Duckweed (Lemna minor D0158): a promising protein source for food security - Basnet, Ramesh; Du, Anping; Tan, Li; Guo, Ling; Jin, Yanglin; Yi, Zhuolin; Huang, Tianfang; Fang, Yang; Hai, Zhao (Banko Janakari, 2024)
Duckweeds, recognized as the fastest growing aquatic flowering plants, exhibit substantial biomass production. Recently, they have been emerged as a potential industrial crop for efficient and eco-friendly protein production and nutrient recovery compared to conventional crops. The objective of the study was to determine the biomass accumulation rate, protein content and amino acid analysis of duckweeds (Lemna minor D0158).We cultured L. minor D0158 from its preserved state in the gene bank into both aseptic (in-vitro) and open condition at controlled room. The medium was Hoagland Solution (HS) mixed with sucrose in in-vitro condition while 1/5 concentration of HS (without sucrose) was in the open condition. Subsequently, we determined the dry biomass growth by calculating the weight difference adopting the Bergmann Method, and then calculated the protein percentage following the Kjeldahl Method. Moreover, the amino acid profiling was obtained using the Hydrolysis and Liquid Chromatography Technique. Later on, we compared the results with those of the other duckweeds and soybean together with the FAO requirements. We found that L. minor D0158 possessed the dry biomass growth rate of 6.72 g/m2/d with 33.13% protein content within 7-day cultivation period. Moreover, it exhibited significantly higher levels of branched chain amino acids (BCCAs) than soybean and met the FAO requirements. However, methionine (Met) content was found to be slightly low. The study suggested that L. minor D0158 might offer a sustainable solution for protein food security in future.